2014
DOI: 10.1007/s10833-014-9241-1
|View full text |Cite
|
Sign up to set email alerts
|

Professional background and working practices of consultants in school development: Initial empirical findings from Germany

Abstract: In Germany, it can be observed that schools increasingly take advantage of experts from the outside in their further pedagogical and organizational development. Regarding their profession and the area of content to which they are assigned, these experts represent a heterogeneous group. This contribution assumes that several patterns can be observed that have to do with the professional background of the consultants as well as with the content and the way these consultants work. It takes up insights from a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…This paper set out to explore what the broad range of new actor constellations means for teachers’ roles and responsibilities by focusing on the contextually specific relations through which teachers’ knowledge work is enacted. The findings provide various insights on this topic and substantiate previous studies that have shown how multiple sets of combined interests, concerns and demands are imposed on teacher professionals and schools (Dedering et al , 2015; Drew et al , 2016; Hall, 2017).…”
Section: Concluding Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This paper set out to explore what the broad range of new actor constellations means for teachers’ roles and responsibilities by focusing on the contextually specific relations through which teachers’ knowledge work is enacted. The findings provide various insights on this topic and substantiate previous studies that have shown how multiple sets of combined interests, concerns and demands are imposed on teacher professionals and schools (Dedering et al , 2015; Drew et al , 2016; Hall, 2017).…”
Section: Concluding Discussionsupporting
confidence: 85%
“…Although the literature on the relationship between specific actors and schools is extensive, few studies have looked at how the diversity of actors together poses new knowledge challenges for teachers’ work. While some researchers have documented how external developmental consultants and coaches increasingly play a significant role in transformations within schools (Dedering et al , 2015; Mayer et al , 2015), others have researched the role of school–university partnerships to foster teachers’ professional development (Bartholomew & Sandholtz, 2009; Lillejord & Børte, 2016). Certain studies have documented the role of local governing agencies, such as school reform support organisations (Datnow & Honig, 2008; Drew et al , 2016) and intermediary organisations to facilitate system‐level and collective learning (Honig, 2004; Rincón‐Gallardo & Fullan 2016).…”
Section: Introductionmentioning
confidence: 99%
“…developing a plan for grade 5–10 students with poor reading and writing skills). Issues can be attributed to the areas ‘teaching development’, ‘organizational development’ and ‘personnel development’ (Dedering, Goecke, & Rauh, 2015).…”
Section: Explaining the Central Termsmentioning
confidence: 99%
“…External advice is widespread in schools. How it is actually carried out and how effective it is have certainly been researched internationally and in German-speaking countries (Dedering et al, 2015). Yet, there are hardly any empirical findings on the specific case of external advice for failing schools .…”
Section: Current State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation